Inscribed Artifacts at Tell Jawa, Jordan: Naoumas' Jug - Daviau, P. M. Michèle (Bulletin of ASOR, 1994)
The transition from the late Byzantine to the early Islamic period was one of considerable changes in language and script, religion, economics, and state organization. At the same time there was a certain amount of continuity that can be seen in the material culture from Umayyad period sites. One example is the jug of Naoumas that was inscribed in Greek with a Semitic name. This interim report explores the archaeological, linguistic, and historical setting of this find, and introduces us to the inhabitants of Tell Jawa.